Density-Dependent Foraging Behaviors on Sympatric Winter Ranges in a Partially Migratory Elk Population - Merrill, Evelyn; Killeen, Joshua; Pettit, Jed; Trottier, Madeline; Martin, Hans; Berg, Jodi; Bohm, Holger; Eggeman, Scott; Hebblewhite, Mark (Frontiers in Ecology and Evolution, 2020)
Many large herbivore populations are partially migratory, in which the population is comprised of both non-migratory (resident) and migratory individuals. Density-dependence contributes to regulating the dynamics of partially migratory populations by altering habitat selection, vital rates, or rates of behavioral switching between migratory tactics. Studies of mechanisms leading to these shifts have focused mainly on their behavior on summer range, overlooking the potential for density-dependent effects during winter that may influence decisions to migrate. We hypothesized that competition for food and safety from wolf predation risk on winter ranges would differentially affect habitat selection, movements, and grouping behavior of migrant and resident female North American elk (Cervus canadensis) on their sympatric winter range. We used GPS locations from 92 adult female elk in 155 elk-winters at Ya Ha Tinda, Alberta, Canada, over a 14-year period when the elk population declined by ∼70% to test our hypotheses. Elk showed consistently strong selection for areas of high forage biomass that corresponded to longer residence times and shorter return times to areas of high forage biomass. The strength of the selection diminished at high elk population size as did the extent to which elk traded off forage for safety from wolf predation risk. Elk increased movement rates and extended return times only to the riskiest areas. Median group size and mean sociality among elk increased at low population size, with resident elk groups being larger and more cohesive than migrant groups. Similar density-dependent responses by migrant and resident female elk on sympatric winter range indicate resident elk do not alter foraging behaviors to compensate for exposure to low nutritional resources in summer, implicating seasonal differences in nutrition are not mediated by winter densities in this system. We discuss the implications of competition on winter ranges for the maintenance of partial migration in ungulates in montane systems.